Development of DC-DC converter for DC motor using neural network controller - Abdullah, Rasyidi (2013)
A neural network of DC-DC converter is designed and presented in this project. In order to control the output speed of the DC-DC converter, the controller is designed to change the duty cycle of the converter. The mathematical model of DC-DC converter and neural network controller are derived to design simulation model. The simulation is developed on Matlab simulation program. To verity the effectiveness of the simulation model, an experimental set up is developed. The neural network controller to generate duty cycle of PWM signal is programmed. The simulation and experimental results will show output speed of the DC-DC converter can be controlled according to the value of duty cycle.